A Qualitative Case Study: Pre-service Teachers as Novice Programmers - ŞENER, Burcu; UMUTLU, Duygu (Journal of computer and education research, 2024)
To meet the needs of 21st-century learners in today’s classrooms, it is needed that teachers be familiar with programming and computational thinking. Particularly, subject-area pre-service teachers should be exposed to programming instruction in their teacher education programs. This case study including three participants aims to explore the process of pre-service teachers’ learning of programming while completing CT-oriented tasks through observations and interviews in a 14-week educational technology course at a public university in Turkey. The findings demonstrate that pre-service teachers, being novice programmers, prefer contextualized, structured and visually well-designed programming tasks. They use various strategies to face challenges, and the effort they put into dealing with these challenges enables them to produce higher-quality programs. Accordingly, implications for further research are also discussed in this study.